2024
DOI: 10.1002/ijc.34849
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in breast cancer cell line research

Manika P Sharma,
Supriya Shukla,
Gauri Misra

Abstract: Breast cancer, a formidable global health challenge, needs continuous translational research to understand the complexity of mechanisms and improve therapeutic and diagnostic strategies. Breast cancer cell lines are of paramount importance as they significantly contribute to the initial stage of research to understand cancer biology. This review provides insights into targeted therapies and immunotherapies that have emerged using in vitro models and microbiome analysis. It focuses on therapeutic development us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 66 publications
(101 reference statements)
0
1
0
Order By: Relevance
“…We revealed that in HBCX-17 and T174 cells, belonging to the mesenchymal subtype (M), GE has a strong toxic effect, without significantly affecting the cell cycle and invasive potential. Regarding variance, in the mesenchymal (M) HBCX-9, and in HBCX-39, classified as basal-like 1 (BL1) by Coussy et al [44], a modest toxic concentration of GE blocked the cell cycle, induced apoptosis, and reduced invasion capability, as in mesenchymal MDA-MB-231 cells [45].…”
Section: Discussionmentioning
confidence: 99%
“…We revealed that in HBCX-17 and T174 cells, belonging to the mesenchymal subtype (M), GE has a strong toxic effect, without significantly affecting the cell cycle and invasive potential. Regarding variance, in the mesenchymal (M) HBCX-9, and in HBCX-39, classified as basal-like 1 (BL1) by Coussy et al [44], a modest toxic concentration of GE blocked the cell cycle, induced apoptosis, and reduced invasion capability, as in mesenchymal MDA-MB-231 cells [45].…”
Section: Discussionmentioning
confidence: 99%